Migration Flows of the “Southern” Christians from the Countries of Tropical Africa to Secular Europe at the Beginning of the 21st Century: The Meeting of “Northern” and “Southern” Christianity - L. A. ANDREEVA (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
In the 21st century we observe revolutionary changes that happen under the influence of globalization. These changes have covered the whole world. On the one hand, they manifest as a rapid shift of the centre of Christianity from the countries of so-called “global North” to the countries of so-called “global South”. On the other hand, they manifest as migration flows of “Southern” Christians from the countries of Tropical Africa to Europe that bring some archaization not only to modern European Christianity but to secular European civilization itself. This paper presents results of the analysis which has shown that modern European values are secular, and European Christianity is rapidly transforming into culture. In comparison to European values, the values of African Christianity have a genuine religious ground, and the society in countries of the Tropical Africa is traditional and being dominated by community values. Therefore, we can conclude that the “Northern” and the “Southern” Christianity exist in different temporal dimensions from the civilizational point of view. We can make a certain prediction that the meeting of “Southern” and “Northern” Christianity in the environment of modern European civilizational code alien to African Christianity will bring lots of challenges to the both branches of Christianity. In the foreseeable future, the issue of mass migration of “Southern” Christians from the countries of Tropical Africa will not be less acute than extensively discussed Islamization of Europe, although both of these issues have similar origin, namely the Renaissance of archaic in Europe brought about by migration flows.